Phytochemical screening, antioxidant activity and antimicrobial activity of Spathodeacampunalata Stem extracts. - Rose Meher; D Manohar Rao; K Ashok Reddy (International Journal of Phytomedicine, 2015)
Spathodeacampunalata is African tulip tree, known for its medicinal properties, in the present study three extracts of stem Ethanolic, Methanolic and Aqueous extracts were evaluated for phenolic content, flavanoid content, total antioxidant capacity by Folin Ciocalteu method ,Colorimetric method, phosphomolybdenum assay respectively.Iinvitro antioxidant activity was evaluated by 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) radical method and by lipid peroxidation method. The antimicrobial activity was evaluated using agar well diffusion assay protocol against eight bacterial reference strains, Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), Proteus vulgaris (ATCC 6380), Salmonella typhimurium (ATCC 25241), Salmonella paratyphi (ATCC 9150), Shigella sonnei (ATCC 25931) and Klebsiella pneumonia (ATCC 27736). Plant sources showing antioxidant activities which is safe has become growing interest across the world thus the above experiment was performed to screen the presence of phytochemicals, estimation of polyphenols, flavonoids, and their ability to show the effects of antimicrobial and antioxidant activities was investigated. Results revealed the presence of phytoconstituents, with relevant quantity of polyphenol and flavonoid content of the extracts was found to decrease in the order of Methanolic extract > ethanolic extract>aqueous extract whereas total antioxidant activity evaluated by phosphomolybdenum assay showed decrease in the order of aqueous extract>methanolic extract>ethanolic extract. The methanolic and ethanolic extracts exhibited better activity against eight bacterial strains used compared to the aqueous extract. Invitro antioxidant activity evaluated by DPPH assay of the extracts showed concentration dependent percentage inhibition of different radicals and raised gradually to its maximum level with higher concentrations, in the lipid peroxidation, aqueous extracts shows less percentage inhibition as compared to methanolic and ethanolic extracts. Thus extract possesses significant antioxidant activity.